Family management and firm performance : moderating effects of professional CEOs - Cheong, Angelina (Nanyang Technological University, 2010)
The purpose of this study is to investigate the effect of family-managed firms on firm performance based on the market performance for public firms listed on the Singapore Stock Exchange (SGX). Using a sample data of 530 SGX-listed firms from prospectuses and annual reports from Osiris, as well as Bloomberg, we obtained 996 observations for both fiscal years 2005 and 2006. Firstly, we looked into the association between family-managed firms and firm performance. Secondly, we looked into whether the presence of a professional Chief Executive Officer (CEO) has any moderating effect on the association between family-managed firms and firm performance. Our results indicated that the proportion of family members on the board has a marginal negative association with firm performance. We also found a marginally significant interaction effect where the presence of a professional CEO lowers the strength of the negative association between the proportion of family members on the board and firm performance.